Review paper Opioid peptides and opiate alkaloids in immunoregulatory processes - Stefano, George B.; Kream, Richard M. (Archives of Medical Science, 2010)
Among the various non-neuronal cell types known to express and utilize neuropeptides, those of the immune system have received much attention in recent years. In particular, comparative studies in vertebrates and invertebrates have shown that endogenous opioid peptides are engaged in receptor mediated autoregulatory immune and neuroendocrine processes. The majority of these immune processes are stimulatory, as determined by their effects on conformational changes indicative of immunocyte activation, cellular motility, and phagocytosis. Endogenous opioid peptides form an effective network of messenger molecules in cooperation with cytokines, opiate alkaloids, and certain regulatory enzymes (neutral endopeptidase 24.11). Peptide-mediated immunostimulatory effects observed in this system are operationally counteracted by the inhibitory effects of morphine and related opiates. Opioid/opiate signaling processes are mediated by several types of receptors with different degrees of selectivity. Among them the recently identified, opioid insensitive µ3 receptor deserves attention on account of its specificity for opiate alkaloids.